Genetic diversity and positive selection analysis of classical swine fever virus isolates in south China - Shen, Haiyan; Pei, Jingjing; Bai, Jialin; Zhao, Mingqiu; Ju, Chunmei; Yi, Lin; Kang, Yanmei; Zhang, Xuetao; Chen, Lijun; Li, Yinguang; Wang, Jiaying; Chen, Jinding (Virus genes, 2011)
Classical swine fever virus (CSFV) causes a highly contagious disease that leads to significant economic losses in the pig industry worldwide. However, there is a paucity of knowledge on the accurate genotyping of CSFV isolates in south China. This study genotyped the E2 gene of 14 CSFV strains isolated during 2008–2010 from domestic pigs in different districts of south China. Phylogenetic analyses revealed that all of the 14 CSFV isolates were clustered into genetic subgroup 1.1. This contrasts with most parts of China, where group 2 isolates are predominant. Furthermore, the positive selection pressures acting on the Erns and E2 envelope protein genes of CSFV were assessed and a site-by-site analysis of the dN/dS ratio was performed to identify specific codons that undergo diversification under positive selection. While no significant evidence for positive selection was observed in Erns, two positively selected sites at amino acid residues 49 and 72 in the E2 encoding region were identified. Our results revealed that a predominance of subgroup 1.1 CSFV isolates is currently circulating in some districts of south China, which appear to be unrelated to the Chinese C-strain vaccine. Moreover, the envelope protein gene, E2, has undergone positive selection in 14 CSFV strains and two positively selected sites have been identified in this study. Understanding the molecular epidemiology and functional importance of these positively selected amino acid positions could help to predict possible changes in virulence, the development of vaccines and disease control.